1975
DOI: 10.1002/1097-0142(197501)35:1<98::aid-cncr2820350115>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Combination versus single agent chemotherapy: A review of the basis for selection of drug treatment of cancer

Abstract: In a period of a little over 20 years, chemotherapy of cancer has evolved from a period of empiricism with little impact on the cancer problem to become part of a sound medical discipline with firm scientific underpinning playing an increasingly important role in the control of cancer. This progress has come from an increasing knowledge of cancer biology and pharmacology and the application of this knowledge to improved design of clinical trials, with due consideration to the intricacies of the natural history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
183
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 370 publications
(185 citation statements)
references
References 32 publications
1
183
0
1
Order By: Relevance
“…Combination therapy plays a significant role in pharmacotherapy (1). One important aspect of combination therapy is the potential for synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy plays a significant role in pharmacotherapy (1). One important aspect of combination therapy is the potential for synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…17 Complete responses were rare. Although it may be possible that response rates for cyclophosphamide may be slightly higher than the rate of 27% reported from early trials, it is extremely unlikely that the partial and complete response rates observed in our patient population could be obtained by cyclophosphamide alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly evident in cancer treatment that simultaneously targeting multiple critical pathways using combinations of chemotherapeutic drugs can enhance outcomes (14)(15)(16)(17). Conventional screening of chemotherapeutics uses an established panel of cancer cell lines (18) that have been derived from bulk tumors.…”
mentioning
confidence: 99%